FATORES ASSOCIADOS À QUALIDADE DE VIDA E SUA RELAÇÃO COM A DEPRESSÃO EM MULHERES OBESAS - Arruda, Talissa Farias (2019)
Introduction: Obesity has been associated with worsening quality of life, but these data are inconsistent and inconclusive due to the possibility that depression is the main link between these two variables (quality of life and depression). Thus, it is necessary to verify factors associated with quality of life and its relationship with depression in obese women from Santa Maria - RS; Methodology: A cross-sectional study was performed. Data collection was performed from September 2017 to December 2018 at the Franciscan University. Depression was assessed by the Beck Depression Inventory (BDI), physical inactivity was assessed by the International Physical Activity Questionnaire (IPAQ), and quality of life by the Brazilian Version of the Quality of Life Questionnaire (SF-36). Results: The sample consisted of 136 women and the mean age was 41.7 ± 10.5 years and showed a mean Body Mass Index (BMI) of 36.0 ± 4.5 kg / m2. Observing the functional domain, we found that women aged 41 - 60 years, who had lower income, with a BMI between 30 - 40 and associated depressive symptoms, had a worse quality of life. In the domains pain, physical, vitality and physical component, there was only relationship regarding depression. And in the general domain, women between 20 - 40 years old who had depressive symptoms had a worse quality of life. Analyzing the social domain, women with depression had a worse quality of life. In the emotional domain, women aged 20-40 years, with higher tertiary income (IEN) and depressive symptoms had a worse quality of life. In the mental domain, women between 20 - 40 years old and with depressive symptoms indicate a worse quality of life. That is, in all domains of the physical component and the mental component were associated with depression. Conclusion: Depression is associated with all domains of quality of life, and it can be concluded that depression is the factor that causes the decrease in quality of life scores of the women analyzed in this sample and not the fact that they are obese.